Pengaruh Audit Tenure dan Komite Audit Terhadap Kualitas Laba Pada Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Indonesia Tahun 2009-2011 - Sayuthi Sayuthi (Al-Buhuts, 2017)
This study aims to provide empirical evidence on the effect of audit tenure and audit committee to earning of quality. The research was conducted at a manufacturing company listed on the Indonesia Stock Exchange in 2009-2011. This type of study is a research verificative or hypothesis testing research. The research method used in this research is census and balanced panel data. Target population in this study is a manufacturing company that has complete data for all variables studied. The population of this study is 39 firms which observed periods are 3 years. The data collection techniques using secondary data from financial statements have been audited and published www.idx.co.id obtained from website to the financial statements in the period 2009-2011. The hypothesis is tested by using multiple regression analysis. This result shows that (1) when there is not audit tenure and audit committee, earning of quality is at 95,4% and is not at 100% (2) audit tenure and audit committee simultaneously have negative influence toward earning of quality (3) Audit tenure and audit committee partially has negative influence toward earning of quality.